Pemphigus: trigger and predisposing factors - Moro, Francesco; Sinagra, Jo Linda Maria; Salemme, Adele; Fania, Luca; Mariotti, Feliciana; Pira, Anna; Didona, Biagio; Di Zenzo, Giovanni (Frontiers in Medicine, 2023)
Pemphigus is a life-threatening autoimmune blistering disease affecting skin and mucous membranes. Despite its etiopathogenesis remains largely unknown, several trigger and predisposing factors have been reported.Pemphigus is caused by autoantibodies that target desmoglein 1 and desmoglein 3, impacting desmosome function. However, circulating autoantibodies are often the consequence of a precipitating factor that occurs in predisposed individuals.This review aims to describe and discuss almost all trigger and predisposing factors reported as possible or probable cause of the disease.Among the reported trigger factors that may induce or exacerbate pemphigus, we have found of particular interest: drug intake (especially thiol-and phenol-containing compounds), vaccines, infections, as well as some reports about pregnancy, radiations, emotional stress, pesticides and physical trauma. Moreover, we discuss the possible role of food intake in pemphigus onset and particular attention is given to dietary factors containing thiol, phenol and tannin compounds.A trigger factor is "the straw that breaks the camel's back", and often acts together with predisposing factors.Here we discuss how pemphigus onset may be influenced by genetic susceptibility and comorbidities like thyroid diseases, malignancies and other autoimmune disorders.To identify other hitherto unknown trigger and predisposing factors, well designed prospective studies are needed. In this context, future research should explore their connection with the aim to advance our understanding of pemphigus pathogenesis.